123I-metaiodobenzylguanidine myocardial scintigraphy with early images alone is useful for the differential diagnosis of dementia with Lewy bodies. (30th March 2017) - Manabe, Yuta; Inui, Yoshitaka; Toyama, Hiroshi; Kosaka, Kenji
Abstract: 123I-metaiodobenzylguanidine cardiac scintigraphy (MIBG) is a useful imaging technique for the diagnosis of dementia with Lewy bodies (DLB). However, MIBG has a serious disadvantage in that it demands a long examination time. The objective of this study was to evaluate statistically the usefulness of the heart/mediastinum ratio (H/M) from the early phase of MIBG for the differential diagnosis of DLB. In total, 113 patients were examined, including 32 non-DLB (19 with Alzheimer's dementia) and 79 DLB patients. The mean early-H/M ratio was 2.83 in the non-DLB group and 1.95 in the DLB group. The mean delayed-H/M ratio was 3.0 in the non-DLB group and 1.76 in the DLB group. With a cutoff point of 2.27 on early images, the sensitivity, specificity, and diagnostic accuracy were 65%, 94%, and 73%, respectively, and the area under the curve was 0.82, indicating moderate accuracy. This analysis indicates that images from the early phase of MIBG alone are sufficient for the differential diagnosis of Alzheimer's disease and DLB. Highlights: MIBG scintigraphy is used for the diagnosis of dementia with Lewy bodies (DLB). MIBG has a serious disadvantage in that it demands a long examination time. We evaluated whether the early images from MIBG alone could be diagnostic. Early MIBG images were sufficiently sensitive, specific, and accurate for DLB. Simplified MIBG may be useful in the differential diagnosis of DLB.